2012
DOI: 10.5505/agri.2012.75537
|View full text |Cite
|
Sign up to set email alerts
|

Cervical epidural steroid injections for symptomatic disc herniations

Abstract: Summary Objectives: Cervical radiculopathy is widespread in society, and the methods used in the treatment cover a wide range from conservative treatment to surgical treatment. There is not yet a full consensus on the use of invasive approaches ÖzetAmaç: Servikal radikülopati toplumda yaygın olup, tedavisinde kullanılan yöntemler konservatif tedaviden cerrahi tedaviye kadar geniş bir aralıkta yer almaktadır. Optimal radiküler ağrı tedavisinde invaziv yaklaşımlar açısından henüz tam bir fikir birliği bulunmamak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The primary goals of surgical interventions are to relieve radiating arm pain in the case of radiculopathy and to prevent progression of neurological deficit in case of myelopathy (27). Cervical epidural injections have been used to treat radicular pain from herniated discs, spinal stenosis, chronic pain secondary to post cervical surgery syndrome, and chronic neck pain of discogenic origin without disc herniation (17,18,(37)(38)(39)(40)(41)(55)(56)(57)(58)(59)(60)(61)(62)(63).…”
Section: Discussionmentioning
confidence: 99%
“…The primary goals of surgical interventions are to relieve radiating arm pain in the case of radiculopathy and to prevent progression of neurological deficit in case of myelopathy (27). Cervical epidural injections have been used to treat radicular pain from herniated discs, spinal stenosis, chronic pain secondary to post cervical surgery syndrome, and chronic neck pain of discogenic origin without disc herniation (17,18,(37)(38)(39)(40)(41)(55)(56)(57)(58)(59)(60)(61)(62)(63).…”
Section: Discussionmentioning
confidence: 99%
“…reported that 70 patients who were suffering from radicular pain from a herniated cervical disc were offered surgical treatment but given the option of a cervical TFESI. It appeared that a large percentage of patients (63.5%) obtained relief of their symptoms with a good/excellent result per Odom criteria and avoided surgery for the follow-up period up to 1 year [ 26 ]. Although there has been sparse literature in reference to cervical TFESI, it suggests benefits for neck pain or/and radicular pain caused by a cervical herniated disc and non-traumatic spondylosis.…”
Section: Discussionmentioning
confidence: 99%
“…Diwan et al (9) in recent systematic review with literature included through December 2011 assessed the evidence with inclusion of 7 randomized trials (251,254,801,802,(1761)(1762)(1763) showing good evidence for cervical disc herniation, and fair evidence for axial or discogenic pain, spinal stenosis, and post cervical surgery syndrome. Our literature search identified 9 new studies (907,(1764)(1765)(1766)(1767)(1768)(1769)(1770)(1771) published since the systematic review (9).…”
Section: Cervical Epidural Injectionsmentioning
confidence: 99%